Investigating the molecular relationships of Arabian toads via mitochondrial 16S rRNA gene analysis in Taif city, Saudi Arabia - Abdulwahed Fahad Alrefaei; Bandar Hamoud Alosaimi; Raed Hamoud Algethami; Javed Ahmad; Rajesh Jeewon (PLoS ONE, 2025)
Taxonomic studies of the Arabian toad (Sclerophrys arabica) are of great interest to better understand phylogenetic relationships and their differences in morphology and distribution. In this study, the genetic diversity and phylogenetic relationships of the Sclerophrys arabica are investigated utilizing the mitochondrial 16S ribosomal RNA (rRNA) gene. Tissue samples from 30 individuals were obtained from various places in Taif, Saudi Arabia, and following DNA extraction, PCR and sequencing, phylogenetic analyses were performed. Phylogenetic investigation using Maximum Likelihood (ML) methods found that S. arabica belongs to a separate clade within the Bufonidae family, closely related to Sclerophrys gutturalis, and exhibits no gene flow with other toad species. Sclerophrys arabica’s strong phylogenetic relationships to other Sclerophrys species support the genus’ monophyly, but its relatively distant position from other species also reflects evolutionary separations within the Bufonidae family. This research demonstrates the utility of the mitochondrial 16S rRNA gene as a reliable genetic marker in amphibian phylogeny, contributing to our understanding of species relationships and providing a basis for future taxonomic and conservation work.